Opportunities and Challenges for Utilizing the Social Potential of Infrastructure toward A Blue Economy - Habibie, Mulia; Masfar, Febi Hendra; Sidabutar, Yuanita FD; Amelia, Cevy (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Since it first became popular around 2008, the blue economy has become an interesting topic in recent years. This principle is the future of water and sea-based economic governance. Geographically, Sijantung Village is located at 0°45'10.7